2021
DOI: 10.1002/tox.23312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead exposure on the activation of microglia in mice fed with high‐fat diets

Abstract: Lead (Pb) exposure can cause central nervous system (CNS) damage. The process of Pb neurotoxicity is accompanied by the microglia activation. In addition, microglia activation was observed under the intervention of high‐fat diets (HFD). This study was designed to investigate the effect of Pb on the cognitive function of mice with HFD, with focus on the microglia activation in brain. Male C57BL/6J mice, 8 weeks of age, were randomly divided into control, HFD, Pb, and HFD + Pb groups. The results showed that HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…proved that an astrocyte subset can have the opposite effect. LAMP1 + TRAIL + astrocytes are distributed near the meninges (the membrane surrounding the brain) and can express the lysosomal protein LAMP1 2 and the death receptor ligand TRAIL 3 . TRAIL proteins can induce the death of T cells that promote inflammation and help to limit CNS inflammation.…”
Section: The Role Of the Brain–gut–microbiota Axis In Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…proved that an astrocyte subset can have the opposite effect. LAMP1 + TRAIL + astrocytes are distributed near the meninges (the membrane surrounding the brain) and can express the lysosomal protein LAMP1 2 and the death receptor ligand TRAIL 3 . TRAIL proteins can induce the death of T cells that promote inflammation and help to limit CNS inflammation.…”
Section: The Role Of the Brain–gut–microbiota Axis In Neuroinflammationmentioning
confidence: 99%
“…Lead has a strong affinity for nerve cells and can cause neurological diseases. Wu et al 2 demonstrated that lead can induce an inflammatory cascade in the CNS by triggering glial cells, disrupting blood-brain barrier (BBB) structure and function, and promoting the release of pro-inflammatory factors. Neuroinflammation triggers neuronal death and leads to neurological damage.…”
Section: Introductionmentioning
confidence: 99%
“…HM,s including Cd, Mn, Hg, As, and Ni, induce impairment of astrocyte functions and direct astrocytic cell death [ 61 ]. Activation of microglia upon exposure to Pb has been shown in mice [ 62 ]. Moreover, the microglia are able to amplify inflammatory activation of astrocytes in Mn-induced neurotoxicity [ 63 ].…”
Section: Mechanisms Of Toxicity Induced By Toxic Metals In Ndmentioning
confidence: 99%
“…Toxic metals are among the most important causes of environmental pollution 1–5 . Lead (Pb) is among the environmentally polluting and toxic metals 6–10 .…”
Section: Introductionmentioning
confidence: 99%